2013
DOI: 10.1248/bpb.b12-00681
|View full text |Cite
|
Sign up to set email alerts
|

<i>Angelica keiskei</i> Ameliorates Scopolamine-Induced Memory Impairments in Mice

Abstract: Memory impairment is the most common symptom in patients with Alzheimer's disease (AD). Angelica keiskei (AK) has traditionally been used as a diuretic, laxative, analeptic and galactagogue. However, the anti-amnesic effects of AK and its molecular mechanisms have yet to be clearly elucidated. The aim of the present study is to evaluate the effects of AK on scopolamine-induced memory impairments in mice. The regulatory effect of AK on memory impairment was investigated using passive avoidance, Y-maze and the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
(29 reference statements)
2
16
0
Order By: Relevance
“…Thus, we examined the effects of HCW in Aβ-injected mice model. Then we continued to work on the study using scopolamine-injected mice, a cholinergic dysfunction model of an antagonist of ACh because scopolamine induce memory deficits are similar to those found in age-related dysfunction in central nervous system and is a useful tool for investigating learning and memory studies which involved in cholinergic system (Oh et al ., 2013). We performed the Y-maze task and PAT to estimate memory consolidation (Conrad et al ., 1996; Roozendaal, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we examined the effects of HCW in Aβ-injected mice model. Then we continued to work on the study using scopolamine-injected mice, a cholinergic dysfunction model of an antagonist of ACh because scopolamine induce memory deficits are similar to those found in age-related dysfunction in central nervous system and is a useful tool for investigating learning and memory studies which involved in cholinergic system (Oh et al ., 2013). We performed the Y-maze task and PAT to estimate memory consolidation (Conrad et al ., 1996; Roozendaal, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as described previously [23] with some modification. BV-2 cells were plated at a density of 1 × 10 6 cells per ml in a 6-well cell culture plate with 2 ml of culture medium and incubated for 24 h. The cells were pre-treated with FCL for 1 h and stimulated with LPS (100 ng/ml) for specified time periods.…”
Section: Methodsmentioning
confidence: 99%
“…5) We previously reported that the ethanolic extract of Angelica keiskei markedly ameliorated scopolamine-induced memory impairments via the inhibition of AChE activity as well as through the activation of cAMP response elementbinding protein (CREB)-brain-derived neurotrophic factor (BDNF) signaling. 6) Using activity-guided fractionation to identify the active compound(s), we isolated the active compounds α-and β-amyrin from the ethanolic extract of A. keiskei. Amyrin is a plant-derived pentacyclic triterpene and is present as either α-amyrin (vicinal methyls in the E ring) or β-amyrin (geminal methyls in the E ring) (Fig.…”
mentioning
confidence: 99%